Pengaruh Gaya Hidup, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Samsung Di Kecamatan Bugul Kidul Kota Pasuruan - Aziz, Abdul; Wahono, Budi; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study investigates how Lifestyle, Price, and Product Quality influence purchasing decisions for Samsung smartphones in Bugul Kidul District, Pasuruan City. Employing multiple linear regression analysis, the research adopts a quantitative, explanatory approach. The sample comprised 80 respondents selected using the Malhotra formula. Data analysis was performed with SPSS version 25, encompassing validity, reliability, normality, classical assumption, hypothesis, and R² coefficient of determination tests. The findings reveal that Lifestyle, Price, and Product Quality collectively impact purchasing decisions significantly. Specifically, Lifestyle and Product Quality positively affect the choice to purchase Samsung smartphones in Bugul Kidul District, whereas Price does not have a notable effect on consumer purchasing decisions. Keywords: lifestyle, price, Product Quality, Purchasing Decisions